AGAMA DAN BUDAYA PATRIARKI: SEBUAH TELAAH KEKERASAN BERBASIS GENDER [RELIGION AND PATRIARCHAL CULTURE: AN STUDY OF GENDER-BASED VIOLENCE] - Putriana, Haryani; Ariani, Sekar Ayu (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2023)
This paper aimed to see how cases of marital rape or rape of a wife in a marriage from the point of view and relation to patriarchal culture and religion were often used as excuses for actions that take away women's rights as wife, and should be treated with good muamalah rule. Forms of violence perpetrated against women were manifestations of gender inequality between men and women, so domination and discrimination against women often occur, such as sexual violence. The type of research used was library research, by looking for literature that was relevant to the topic of discussion, namely religion, patriarchal culture, marital rape, and counseling. This research used secondary data such as scientific articles, online newspapers, books, and others which were included and in accordance with the discussion of gender based violence as the focus of the case of marital rape. The collected data then were analyzed. The results of this study were that marital rape was the result of the values contained in patriarchal culture supported by religious doctrines which were only interpreted textually as justification for the actions taken by husbands against their wives. Feminist counseling could be an alternative assistance given to victims of marital rape in understanding their situation and rights as women in the household.